Preparing Graduates for the 21st Century Workplace: A Transdisciplinary Approach to Information Technology-Related Study Programs - Stephanie Swartz (Interdisciplinary Journal of Partnership Studies, 2025)
This paper discusses the importance of integrating global virtual team projects into Information Technology (IT) and Computer Science curricula to enhance students’ cultural awareness and ability to collaborate across different time zones, as well as improve their skills in digital communication and virtual project management. In this study, students enrolled in an IT program at a university in Germany participated in a Collaborative Online International Learning (COIL) project involving peers from 17 different countries and various disciplines. A mixed-methods study was carried out over two semesters, and the results highlight the benefits of such transdisciplinary initiatives, demonstrating the value of incorporating COIL projects into IT curricula, and illuminate the challenges of COIL projects for both students and instructors. With this study, the author aims to encourage educators and administrators in Higher Education to support and implement interdisciplinary COIL projects, better preparing graduates for the challenges of the 21st-century global workforce.